NIAT PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA USAHA MIKRO KECIL MENENGAH DI YOGYAKARTA - Muhammad Muthahhari; Heru Kurnianto Tjahjono; Meika Kurnia Puji RDA (Universitas Muhammadiyah Yogyakarta, 2020)
The aim of this study is to find out behavior institutions in using information and communication technology among Micro Small Medium Enterprise (MSME) in Yogyakarta. Based on unified theory of Acceptance and Use of Technology (UTAUT) model. This study examine whether performance expectancy, effort expectancy, and social influence are the importance antecedent to explain intentions in using ICT (Information and communication technology) among MSME. This study also examine the effect of propensity to act as the moderator in model. There are 164 MSME owners in Yogyakarta as a sample of this study which used purposive technique and analyzed by SEM. The result of this study showed that the performance expectancy and effort expectancy are supported to explain intention use ICT in MSME. Therefor, social influence does not has significant to predict intentios use ICT. The other findings showed that propensity to act has moderation effect on the relation between performance expectancy, effort expectancy, and social influence and behavior intentions.